The Stoic concept of phantasia: from Zeno to Chrysippu - Dinucci, Aldo Lopes (Revista Archai, 2017)
In this paper we will deal with the question of the translation of the term phantasia, with closely related concepts, with the distinction between Cleanthus’ conception of phantasia and the developments made by Chrysippus.